Canadian Women's Experience of Postnatal Care: A Mixed Method Study. Issue 4 (December 2022) - Dol, Justine; Hughes, Brianna; Tomblin Murphy, Gail; Aston, Megan; McMillan, Douglas; Campbell-Yeo, Marsha
Background: The postnatal period remains unstandardized in terms of care and postnatal visits with a dearth of information on the experience from Canadian women. Purpose: To explore (1) with whom and how often women receive postnatal follow-up visits and (2) the postnatal care experiences of Canadian mothers. Methods: Using a cross-sectional design, women who had given birth within the past 6 months were recruited to complete an online survey. Frequencies were computed for quantitative outcomes and thematic analysis was used for qualitative responses. Results: A total of 561 mothers completed the survey. Women saw on average 1.9 different postnatal healthcare providers, primarily family doctors (72.4%). 3.2% had no postnatal visits and 37.6% had 4  or more within 6 weeks. 76.1% women were satisfied with their postnatal care. Women's satisfactory care in the postnatal period was associated with in-person and at home follow-ups, receiving support, and receiving timely, appropriate care for self and newborn. Unsatisfactory care was associated with challenges accessing care, experiencing gaps in follow-up visits, and having unsatisfactory assessment for their own recovery. Conclusion: There is considerable variation in the timing and frequency of postnatal visits. While many women are experiencing satisfactory care, women are still reporting dissatisfaction and are facing challenges.